An aerial view of Oslo, Norway - Bain, Jack (1966)
Jack and Isabel Bain from Brisbane, Queensland, Australia did a ten month round the world post retirement trip in 1966. Oslo (/ˈɒzloʊ/ OZ-loh, US also /ˈɒsloʊ/ OSS-loh, Norwegian: [ˈʊ̂ʂlʊ] ⓘ or [ˈʊ̂slʊ, ˈʊ̀ʂlʊ]; Southern Sami: Oslove) is the capital and most populous city of Norway. It constitutes both a county and a municipality. The municipality of Oslo had a population of 709,037 in 2022, while the city's greater urban area had a population of 1,064,235 in 2022, and the metropolitan area had an estimated population of 1,546,706 in 2021. (Wikipedia)